Development of E-Module Based on Cirebon Local Environment in Fostering Eco-Literacy of Student - Maulana, Ovi Syafiatul; Surtikanti, Hertien Koosbandiah; Amprasto, Amprasto (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to develop e-modules based on the local Cirebon environment related to environmental changes that occur in the Cirebon region as a source of high school student learning to foster the eco-literacy of the student. The method in this research used to research and development (R&D) with the ADDIE model (analysis, design, development or production, implementation or delivery and evaluations). Data collection was conducted through observation, interviews, questionnaires, tests, and documentation. The development of e-modules was validated aspects of eligibility by material experts, technology experts, and users as measured by the validation sheet as well as student responses regarding the emodules as measured by a questionnaire. Meanwhile, the readability test given to students is carried out to ensure the quality of the e-modules as measured by the cloze test. In addition, the eco-literacy of the student was measured by an attitude questionnaire to find out how students' awareness and concern for the surrounding environment. Data were analyzed by qualitative methods. The results showed: 1) the feasibility of the e-module based on the validation of the material experts obtained 95.68% with a very good category, the validation of technology experts with a percentage of 72% categorized as good, and the validation of the teacher, as a user, showed a percentage of 75% with a good category, 2) the results of the cloze test analysis show that e-module has a high level of readability with a percentage of 92.46%, 3) student responses regarding e-modules obtained a percentage of 78.8% with a good category, 4) eco-literacy of students are shown by the results of questionnaire obtained an index of 4.04 with a high category. Products have been revised based on suggestions and corrections from validators and limited trial results. E-module based on the Cirebon local environment in fostering eco-literacy of students can be implemented in classroom learning